(untitled) (International Journal of Engineering and Computer Science, 2014)
Android is now the most used mobile operating system in the world. Android now has more users, more phones and more tablets worldwide than any other mobile operating system. One of the most difficult challenges facing testing teams is their ever changing and evolving configurations. The number of mobile device variations in the marketplace is quite staggering. Dozens of new mobile devices, such as Smart Phones, are being released monthly by device manufacturers, many with incremental operating system features and enhancements, which are further adding to the variation of configurations of these devices. Also application development life cycle for android is very short and hence testing time is squeezed. Testing of application across different version of android is a challenge. In this paper we present an approach for automating the testing process for Android applications, with a focus on GUI and functional bugs.